PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KONTEKSTUAL PADA MATERI TEKS PROSESUR KELAS VII SMP - Kartika, Dewi; Kusyani, Diah; Nurhayati, Nurhayati (Universitas Islam Sumatera Utara, 2024)
The aim of this research is to develop a contextually based student worksheet product on procedure text material. The research method used in this research isResearch and Development (RD) using a development modelADDIE (Analysis, Design, Development or Production, Implementation or Delivery dan Evaluations). This research was conducted in 4 SMP/MTs schools to obtain 12 Indonesian language teachers' responses to the products that had been developed. Classification of 3 teachers from SMP Al Washliyah 8 Medan as primary data and 9 Indonesian language teachers as supporting/secondary data. The stages in this development are needs analysis, product design, product development, validation of material and media experts, and assessment of the feasibility of student worksheets. Data collection was carried out through observation, interviews, questionnaires, and documentation. This research uses quantitative descriptive data analysis techniques which are then converted to qualitative data using a Likert scale. Based on the validation results from material experts, this student's worksheet received a score of 91.1 and after being averaged it became 4.5 in the very good category. Meanwhile, as a result of media expert validation, this student's worksheet received a score of 91.4 and after being averaged it became 4.5 in the very good category. The assessment results from Indonesian language teachers obtained a score of 84.8 with an average score of 4.2 in the very good category. Thus, contextually based student worksheets on procedure text material for class VII middle school students are declared suitable for use as teaching materials.